Pemberdayaan Guru Sekolah Mengenai Keselamatan Berlalu Lintas: Empowering School Teachers Regarding Traffic Safety - Siswanto, Joko; Apriyanto, Rizal; Tohom, Frans; Widiandaru, Nanang Okta; Fahmadi, Aat Eska; Ikapraja, Bagus (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The behavior of drivers in the Tegal City school community often violates traffic rules because they do not understand and are not aware of traffic safety. Increased knowledge, understanding, awareness and skills of teachers regarding traffic safety need to be increased and empowered more massively. Empowering school teachers regarding traffic safety includes 4 stages (preparation, initial test, community empowerment, and final test) with traffic safety community results. 240 PAUD/TK/RA, SD/MI, SMP/MTs, and SMA/SMK/MA teachers as participants for 2 days with 7 topics. The majority of participants consisted of bachelor's degrees (89.6%), women (55.8%), ages 36-46 (35%), and PAUD teachers (25.8%). The initial test for 7 topics is still between 20%. Activities on the first day are stages 1-4 and on the second day stages 5-7. The final test of 7 topics is above 75%. 7 topics had an increase of more than 55%. Increasing school teachers' knowledge has an impact on imparting knowledge to students about traffic safety which can be a step to reduce the occurrence of accidents on the road.